Pengaruh Pajak Karbon, Green Capital Expenditure, dan Intensitas Energi terhadap Profitabilitas Perusahaan Industri dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Nuraidah; Eka Julianti Efris Saputri; Azwani Aulia (ARZUSIN, 2026)
Climate change and the implementation of carbon tax policies have encouraged companies to improve energy efficiency and invest in environmentally friendly initiatives. However, findings regarding the effects of carbon tax, green capital expenditure, and energy intensity on corporate profitability remain inconsistent, particularly among industrial and chemical sector companies in Indonesia. This study aims to analyze the effects of carbon tax, green capital expenditure, and energy intensity on corporate profitability, both partially and simultaneously. This study employed a quantitative approach using a causal associative method. The research population comprised 113 industrial and chemical sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period, with a sample of 10 companies selected through purposive sampling. Data obtained from financial statements, annual reports, and sustainability reports were analyzed using panel data regression with the assistance of EViews 14. The findings show that, partially, carbon tax and energy intensity have no significant effect on profitability, whereas green capital expenditure has a positive and significant effect on profitability. Simultaneously, carbon tax, green capital expenditure, and energy intensity have a significant effect on corporate profitability. This study concludes that investment in environmentally friendly assets plays an important role in improving corporate financial performance, whereas carbon tax implementation and energy intensity did not exert significant individual effects during the study period. These findings emphasize the importance of increasing green investment as part of corporate sustainability strategies and provide input for the government in refining policies for the transition toward a low-carbon economy.